Toward a Pauline Hermeneutic of Dialogue - Solon, Dennis (Silliman Journal, 2022)
Paul’s letter to the Romans can serve as a methodological tool for present-day Filipino Christians in engaging their Muslim counterparts. In this letter, Paul encourages his readers to engage each other in love and acceptance. Although the conflicting parties described in this letter both belong to the same group of Jesus‘ followers, they can nevertheless be seen as representing differing cultures and religious convictions. Hence, Filipino Christians can draw lessons from this letter about some significant and positive ways for dealing with peoples of other religious persuasions.